(untitled) (Third Sector Social Economic Review, 2025)
Large-scale natural disasters, such as earthquakes, generate large amounts of waste that, if not managed effectively, pose serious long-term environmental, economic and public health threats. Although there have been several studies on post-earthquake debris management, there is a significant gap in the literature on its impact on post-disaster recovery processes, especially from sustainability, zero waste and circular economy perspectives. By comparatively analyzing the 2008 Sichuan and 2023 Turkey-Syria earthquakes, this study aims to assess the role of sustainable practices in disaster waste management and identify the most appropriate management model that will contribute to reducing social and ecological impacts through recycling-oriented strategies, resilient construction policies and national waste management standards. However, the decision-making process in this context is complicated by multiple criteria and alternatives. Therefore, the development of sustainable disaster management policies and circular economy-based debris management practices in earthquake-prone regions requires the adoption of new decision-making approaches based on integrated, comparative and multi-criteria analysis of environmental problems. In this way, it will be possible to manage the large amount of waste generated by disasters more effectively, minimize environmental damage and ensure a recovery process in line with sustainable development goals.